USES AND PERCEIVED BENEFITS OF GREEN SPACES IN BUENOS AIRES USOS Y BENEFICIOS PERCIBIDOS EN ESPACIOS VERDES EN BUENOS AIRES - Craik, Jonathan; Faggi, Ana; Miguel, Sebastian; Vorraber, Leslie (European Scientific Journal, ESJ, 2015)
Urban green spaces provide a full range of community benefits (physical, environmental, psychological and social) but some parks types appear differentially important in providing certain benefit types. In this study we analyzed quality and perception of two parks and two plazas in Caballito and Flores neighbourhood (Buenos Aires city). We used the green flag index for green spaces´ quality and interviews (n:232) to explore people`s perception asking 10 questions, four referred to public spaces in general and six referred to the selected green spaces in both neighbourhoods. Results showed that parks and plazas are valued spaces, different visited by residents or by people coming elsewhere attracted by high-quality green spaces. Our findings showed that size and the offer of activities/infrastructure play a role in how a green space is used and how different benefits are recognised and perceived.